A point mutation in the extracellular domain of L1 blocks its capacity to confer metastasis in colon cancer cells via CD10 - Haase, G.; Gavert, N.; Brabletz, Thomas; Ben-Ze'Ev, A. (Oncogene, 2017)
The neural L1 transmembrane cell adhesion receptor of the immunoglobulin-like family is a target gene of Wnt-?-catenin signaling in human colorectal cancer (CRC) cells and is expressed at the invasive edge of the tumor tissue. L1 overexpression in cultured CRC cells confers enhanced proliferation, motility and liver metastasis. We have analyzed the mechanisms of L1-mediated signaling in CRC cells by using various point mutations in the L1 ectodomain that are known to cause severe genetically inherited mental retardation disorders in patients. We found that all such L1 ectodomain mutations abolish the ability of L1 to confer metastatic properties in CRC cells. Using gene array analysis, we identified L1-mutation-specific gene expression signatures for the L1/H210Q and L1/D598N mutations. We identified CD10, a metalloprotease (neprilysin, neutral endopeptidase) and a gene that is specifically induced in CRC cells by L1 in an L1/H210Q mutation-specific manner. CD10 expression was required for the L1-mediated induction of cell proliferation, motility and metastasis, as suppression of CD10 levels in L1-expressing CRC cells abolished the L1 effects on CRC progression. The signaling from L1 to CD10 was mediated through the L1-ezrin-NF-?B pathway. In human CRC tissue L1 and CD10 were localized in partially overlapping regions in the more invasive areas of the tumor tissue. The results suggest that CD10 is a necessary component conferring the L1 effects in CRC cells. The identification of gene expression patterns of L1-domain-specific point mutations may provide novel markers and targets for interfering with L1-mediated CRC progression.
EVALuna2:10219